1970
DOI: 10.1055/s-0028-1095054
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations and Rates of Plasma Clearance and Production of Cortisol and Corticosterone in Healthy Persons and in Subjects with Asymptomatic and Clinical Diabetes Mellitus

Abstract: In three groups of persons, 1) 19 healthy individuals, 2) nine patients with asymptomatic diabetes mellitus, and 3) eight patients with clinical diabetes mellitus, the plasma c1earance rates (CR) of cortisol and corticosterone were estimated simultaneously by means of an intravenous infusion of a tracer dose of both tritium labeled hormones at a constant rate until a steady state was reached (constant infusion technique). The plasma concentrations (C) of each of the two endogenous hormones were measured separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
3
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…The current mean daily FPR of 27.3 ± 7.5 /*mol/day (9.9 ± 2.7 mg/day) or 15.7 /unol/day-m 2 (5.7 mg/m 2 -day) determined in 12 normal volunteers is significantly lower than the FPR reported by previous investigators (1-8). However, this value is closer to that reported by other investigators (11)(12)(13). As expected, FPR varied during the day, with the peak production rate between 0400-0800 h, and the nadir between 2000-2400 h. The pattern of circadian variation in FPR in normal subjects has not been reported previously due to the limiting factor of radiation exposure.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The current mean daily FPR of 27.3 ± 7.5 /*mol/day (9.9 ± 2.7 mg/day) or 15.7 /unol/day-m 2 (5.7 mg/m 2 -day) determined in 12 normal volunteers is significantly lower than the FPR reported by previous investigators (1-8). However, this value is closer to that reported by other investigators (11)(12)(13). As expected, FPR varied during the day, with the peak production rate between 0400-0800 h, and the nadir between 2000-2400 h. The pattern of circadian variation in FPR in normal subjects has not been reported previously due to the limiting factor of radiation exposure.…”
Section: Discussionsupporting
confidence: 89%
“…fluorometry) (2,(8)(9)(10). It is noteworthy that some investigators have reported lower values of FPR using radiotracers (11)(12)(13).…”
mentioning
confidence: 99%
“…The magnitude of the effect of ABCC1 on steroid export appears to be substantial, with a 3-4 fold increase in intracellular corticosterone when ABCC1 is inhibited in SGBS cells, and a 2-fold increase in adipose corticosterone in vivo in mice. In a physiological context, if the plasma glucocorticoid pool is comprised of 90-95% cortisol and 5-10% corticosterone, as reported in previous studies (10,13,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) (table S3), the total (cortisol plus corticosterone) intra-adipose glucocorticoid pool may be reduced by as much as ~7% as a result of ABCC1 activity. In a pathological context, we hypothesized that reduction of adipose ABCC1 in obesity might contribute to metabolic dysregulation through increased intra-adipose corticosterone.…”
Section: Discussionsupporting
confidence: 54%
“…In children only scant information i s available. Our results correspond best to the values reported by Ferrante (8) and Huther & Scholz (15). The former author used protein binding, the latter fluorimetry as end-point.…”
Section: Discussionsupporting
confidence: 91%